KONDISI PENDIDIKAN ISLAM PADA ERA PENJAJAHAN BELANDA DI INDONESIA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article explores the condition of Islamic education in Indonesia during the Dutch colonial period, focusing on its dynamics, policies, and the role of key Islamic education figures in preserving religious and national identity. At that time, Islamic education faced pressure from a colonial system oriented toward Westernization and Christianization. Nevertheless, pesantren, madrasah, and surau remained independent centers of learning rooted in Islamic values. This study employs a qualitative approach through literature review to trace the social history of Islamic education in Indonesia, including analysis of colonial policies, emerging educational institutions, and the contributions of prominent figures such as KH. Agus Salim, Hj. Rangkayo Rasuna Said, and Ki Hajar Dewantara. The findings reveal that Islamic education persisted and developed despite colonial suppression, serving as a vital foundation for the struggle for independence and the shaping of national character.